Political History of the 1964 coup and the military regime: balances and perspectives (Tempo e Argumento, 2024)
This article proposes a historiographical assessment of the field of political history on the 1964 coup d’ État and the military regime in Brazil, while suggesting new perspectives of analysis centered not only on the “coup process” itself, but also on two other themes: the functioning of the policy of the military regime, with emphasis on the articulation between legal repression and State terrorism and the turbulent history of “Political Opening” as a result of dialectic between the authoritarian regime and the field of democratic resistance in civil society. Finally, the text also highlights the importance of criticizing the social memory of the period, aiming to review the periodization consecrated by the moderate liberals that reduces the dictatorial character of the regime itself to the period of the “years of lead” (1969-1974).
Keywords: military regime - political history; political history - military dictatorship; Brazil - political history; Brazil - political repression